3D Ta3N5 thin film confined-growth Co nanoparticles for efficient bifunction electrolyzed water. (10th September 2021) - Gao, Yuanfeng; Tong, Zhaomin; Fan, Xiujun
Highlights: The Co-Ta3 N5 catalysts were successfully prepared by in situ confined growth of active catalytic species within porous nanofilm using Ta3 N5 as templates. The Co-Ta3 N5 nanohybrid is a cheap and earth-abundant bifunctional electrocatalyst for OER and HER. The Co-Ta3 N5 can exhibit outstanding catalytic HER in a wide range of pH media. The Co-Ta3 N5 catalyst exhibited outstanding electrochemical stability. The outstanding HER and OER catalytic performance of Co-Ta3 N5 -800 has surpassed that of most current cobalt-containing catalysts. Abstract: The abundant water resources from the earth are natural feedstocks for the electrolysis of water to produce hydrogen, and there is an urgent need for an efficient and stable catalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Exploration of noble-metal-free, highly-efficient and durable bifunctional catalysts for HER and OER remains a challenge. In this work, Co-Ta3 N5 catalysts were successfully prepared by in situ confined growth of active catalytic species within porous nanofilm using three-dimensional (3D) tantalum nitride (Ta3 N5 ) porous nanofilm as templates. After electrochemical testing, we found that Co-Ta3 N5 nanohybrid exhibits excellent OER and HER performance. Benefiting from the 3D composite nanostructures, the catalysts have excellent electron conduction rates and sufficient active sites, the Co-Ta3 N5 nanocomposites nitrided at 800 °C exhibits relatively good catalytic activity for HER in acidic (low overpotential of 59.1 mV at 10 mA cm −2, small Tafel slope of 58 mV dec −1 ) and alkaline (low overpotential of 93 mV at 10 mA cm −2, Tafel slope of 97 mV dec −1 ) media, respectively. Co-Ta3 N5 -800 also exhibits relatively good catalytic activity for OER with low overpotentials 358 mV at 10 mA cm −1 in 1M KOH and the Tafel slope of 58.5 mV dec −1 . Additionally, Co-Ta3 N5 -800 possesses excellent catalytic performance, and its catalytic performance with almost no degradation in catalytic performance after severe electrochemical tests, which ascribe to the structure of cobalt nanoparticles that confined-growth in Ta3 N5 nanotubes. This discovery may pave a new avenue toward the development of robust inexpensive electrocatalysts for OER and HER.